Effects of Yu-Ping-Feng polysaccharides on animal growth performance and immune function: a review - Chu, Huangbin; Zong, Yi; Yang, Hong; Chen, Siyu; Ma, Zheng; Li, Hua (Frontiers in Veterinary Science, 2023)
Yu-Ping-Feng polysaccharides (YPF-P) is the primary component of Yu-Ping-Feng San (YPF-S) medicine prescription, which consists of three polysaccharides from Astragalus Membranaceus polysaccharide (AM-P), Atractylodes Macrocephala polysaccharide (AM-P), and Saposhnikovia Divaricata polysaccharide (SD-P). The use of Yu-Ping-Feng polysaccharides dates back to the Yuan Dynasty when Yilin Wei first utilized it. The remedy is included in “Effective Formulae Handed Down for Generations” and “The Pharmacopoeia of the People’s Republic of China.” Yu-Ping-Feng polysaccharides is known to promote growth and enhance the body’s immune function in animals. As such, it has promising application prospects in animal husbandry. This review mainly introduces the main components and characteristics of Yu-Ping-Feng polysaccharides, its effects on animal production, and its impact on animal immune function. Additionally, this paper offers a preliminary discussion on the development and utilization of Yu-Ping-Feng polysaccharides, laying the foundation for further research and application. This review may also provide insight and reference for the development of the farming industry, reducing production costs and improving productivity.